Immigration and Opportuntity : Race, Ethnicity, and Employment in the United States - Bell-Rose, Stephanie; Bean, Frank D. (Book collections on Project MUSE., 1999)
"The American dream of equal opportunity and social mobility still holds a powerful appeal for the many immigrants who arrive in this country each year. But if immigrant success stories symbolize the fulfillment of the American dream, the persistent inequality suffered by native-born African Americans demonstrates the dream's limits. Although the experiences of blacks and immigrants in the United States are not directly comparable, their fates are connected in ways that are seldom recognized. Immigration and Opportunity brings together leading sociologists and demographers to present a systematic account of the many ways in which immigration affects the labor market experiences of native-born African Americans."--Jacket.